2018
DOI: 10.1186/s13054-018-1966-4
|View full text |Cite
|
Sign up to set email alerts
|

Implications for paediatric shock management in resource-limited settings: a perspective from the FEAST trial

Abstract: BackgroundAlthough the African “Fluid Expansion as Supportive therapy” (FEAST) trial showed fluid resuscitation was harmful in children with severe febrile illness managed in resource-limited hospitals, the most recent evidence reviewed World Health Organization (WHO) guidelines continue to recommend fluid boluses in children with shock according to WHO criteria “WHO shock”, arguing that the numbers included in the FEAST trial were too small to provide reasonable certainty.MethodsWe re-analysed the FEAST trial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 25 publications
2
20
0
1
Order By: Relevance
“…MDR was de ned as acquired non-susceptibility to at least one agent in three or more antimicrobial categories, XDR was de ned as non-susceptibility to at least one agent in all but two or fewer antimicrobial categories (i.e. bacterial isolates remain susceptible to only one or two categories) and PDR (pandrug resistant) was de ned as non-susceptibility to all agents in all antimicrobial categories [16] .According to CLSI criteria, we de ned infection as follow:1) Blood stream infection: Patient has fever and has a recognized pathogen cultured from 1 or more blood cultures and organism cultured from blood is not related to an infection at another site, or had hemodynamic instability.2) Ventilator associated pneumonia (VAP): Patients with new or progressive and persistent in ltrate in X-rays, with new onset of purulent sputum, change in the character of sputum, more suctioning requirements or worsening gas exchange.3) Central line-associated bloodstream infection: A central line-associated bloodstream infection was de ned as a patient who had at least 1 of the following signs or symptoms: hypothermia or hyperthermia, apnea and positive laboratory results not related to an infection at another site that were central venous line-associated with the central venous catheter having been in place at the time of, or within 48 hours before, the onset of bacteremia. 4) Meningitis: Meningitis was de ned as a patient had organisms cultured from cerebrospinal uid (CSF), as well as who had at least 2 of the following signs or symptoms with no other recognized cause: headache, dizziness, fever, localizing neurologic signs, changing level of consciousness, or confusion.…”
Section: Methodsmentioning
confidence: 99%
“…MDR was de ned as acquired non-susceptibility to at least one agent in three or more antimicrobial categories, XDR was de ned as non-susceptibility to at least one agent in all but two or fewer antimicrobial categories (i.e. bacterial isolates remain susceptible to only one or two categories) and PDR (pandrug resistant) was de ned as non-susceptibility to all agents in all antimicrobial categories [16] .According to CLSI criteria, we de ned infection as follow:1) Blood stream infection: Patient has fever and has a recognized pathogen cultured from 1 or more blood cultures and organism cultured from blood is not related to an infection at another site, or had hemodynamic instability.2) Ventilator associated pneumonia (VAP): Patients with new or progressive and persistent in ltrate in X-rays, with new onset of purulent sputum, change in the character of sputum, more suctioning requirements or worsening gas exchange.3) Central line-associated bloodstream infection: A central line-associated bloodstream infection was de ned as a patient who had at least 1 of the following signs or symptoms: hypothermia or hyperthermia, apnea and positive laboratory results not related to an infection at another site that were central venous line-associated with the central venous catheter having been in place at the time of, or within 48 hours before, the onset of bacteremia. 4) Meningitis: Meningitis was de ned as a patient had organisms cultured from cerebrospinal uid (CSF), as well as who had at least 2 of the following signs or symptoms with no other recognized cause: headache, dizziness, fever, localizing neurologic signs, changing level of consciousness, or confusion.…”
Section: Methodsmentioning
confidence: 99%
“…It should also be noted that children with gastroenteritis were excluded from FEAST, as ongoing fluid losses should be replaced with IV or oral rehydration as indicated. A recent analysis of children with "moderate" hypotension who were randomized to either fluid bolus or maintenance fluid in the FEAST trial was published after completion of our initial systematic review but considered by the panel to be potentially influential [188]. In this analysis, only children with moderate hypotension were included because children with severe hypotension were not allocated to the control (no bolus) arm.…”
Section: We Recommend Removal Of Intravascular Access Devices That Armentioning
confidence: 99%
“…In such paediatric patients, a conservative 10 mL/kg FBT (and not 20 mL/kg) can be used and repeated up to three times 3. However, in our post hoc analysis of the FEAST trial data, we found a general 3% increase in mortality from FBT across all FEAST trial subgroups, including the 65 cases meeting the WHO ‘strict shock’ criteria FBT 4. Second, in the 2014 American College of Critical Care Medicine (ACCM) clinical guidelines for haemodynamic support of neonates and children with septic shock,5 there have been no changes since the 2007 guidelines 6.…”
mentioning
confidence: 80%